Recombinant Production of Biliverdin IXβ and δ Isomers in the T7 Promoter Compatible Escherichia coli Nissle - Robinson, Elizabeth A.; Frankenberg-Dinkel, Nicole; Xue, Fengtian; Wilks, Angela (Frontiers in Microbiology, 2021)
The ability to obtain purified biliverdin IX (BVIX) isomers other than the commercially available BVIX is limited due to the low yields obtained by the chemical coupled oxidation of heme. Chemical oxidation requires toxic chemicals, has very poor BVIX yields (<0.05%), and is not conducive to scalable production. Alternative approaches utilizing recombinant E. coli BL21 expressing a cyanobacterial heme oxygenase have been employed for the production BVIXa, but yields are limited by the rate of endogenous heme biosynthesis. Furthermore, the emerging roles of BVIXb and BVIXd in biology and their lack of commercial availability has led to a need for an efficient and scalable method with the flexibility to produce all three physiologically relevant BVIX isomers. Herein, we have taken advantage of an optimized non-pathogenic E. coli Nissle (EcN(T7)) strain that encodes an endogenous heme transporter and an integrated T7 polymerase gene. Protein production of the Pseudomonas aeruginosa BVIXb and BVIXd selective heme oxygenase (HemO) or its BVIXa producing mutant (HemOa) in the EcN(T7) strain provides a scalable method to obtain all three isomers, that is not limited by the rate of endogenous heme biosynthesis, due to the natural ability of EcN(T7) to transport extracellular heme. Additionally, we have optimized our previous LC-MS/MS protocol for semi-preparative separation and validation of the BVIX isomers. Utilizing this new methodology for scalable production and separation we have increased the yields of the BVIXb and -d isomers >300-fold when compared to the chemical oxidation of heme.